1960
DOI: 10.1111/j.1748-1716.1960.tb01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Disruption of Rat Mesentery Mast Cells Caused by Compound 48/80, Antigen‐Antibody Reaction, Lecithinase A and Decylamine

Abstract: Högberg, B. and B. Uvnas. Further observations on the disruption of rat mesentery mast cells caused by compound 48/80, antigen‐antibody reaction, lecithinase A, and decylamine. The influence of pH, ionic milieu, temperature and enzyme inhibitors, on the disrupting action on rat mesentery mast cells of compound 48/80, antigen and decylamine has been investigated. A pH optimum around 7.4, the essentiality of Ca++ ions, the influence of temperature and the inhibitory action of various enzyme inhibitors, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
2

Year Published

1960
1960
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(34 citation statements)
references
References 11 publications
3
29
0
2
Order By: Relevance
“…Maximal histamine release induced by A23187 was achieved between 33-39°C and the release declined above and below this temperature range. Essentially the same effect of temperature on anaphylactic histamine release from guinea pig lung and antigen induced mast cell disruption was reported by Schild (1957) andHogberg &Uvnas (1960).…”
Section: Cs Wi Lcoxsupporting
confidence: 49%
See 1 more Smart Citation
“…Maximal histamine release induced by A23187 was achieved between 33-39°C and the release declined above and below this temperature range. Essentially the same effect of temperature on anaphylactic histamine release from guinea pig lung and antigen induced mast cell disruption was reported by Schild (1957) andHogberg &Uvnas (1960).…”
Section: Cs Wi Lcoxsupporting
confidence: 49%
“…We conclude that atropine in a low concentration blocks prejunctional muscarinic receptors; at higher concentrations it blocks in addition prejunctional aadrenoceptors. Anaphylactic histamine release from guinea pig lung and disruption of rat mast cell due to antigen is dependent on temperature (Mongar & Schild, 1957;Hogberg & Uvnas, 1960), and on oxidative or glycolytic metabolism (Parrot, 1942;Moussatche & Prouvost-Danon, 1962). The amount of histamine released by the antigen-antibody reaction in vitro was dependent on mast cell ATP content and during the release there was an increased utilization of ATP (Johansen & Chakravarty, 1975).…”
Section: Cs Wi Lcoxmentioning
confidence: 99%
“…Second, a cell regula tory role exists for zinc. For example, zinc antagonizes calcium in various cells [2][3][4][5][6][7][8]. We suggested that zinc might play a regula tory role in numerous cell types through in hibition of the function of the calcium-acti vated protein, calmodulin [9], Third, in addi tion to these fundamental roles, zinc has sev eral uses in clinical medicine, the first of which is the treatment o f zinc deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the observation that CN inhibition does not require pre-incubation of the tissue with CN suggests that this inhibition does not result from depletion of energy stores but rather from inactivation of enzymes other than cytochrome oxidase. Other workers have found that a nitrogen atmosphere did not inhibit antigen-induced rat mast-cell degranulation (Hogberg & Uvnas, 1960), and 5 mm CN was needed to inhibit this reaction (Mota, 1960). Thus, in the rat as in the guinea-pig the effect of CN might well be unrelated to inhibition of aerobic metabolism.…”
Section: Lopmentioning
confidence: 99%